Early Recognition and Diagnosis of Buried Bumper Syndrome: A Report of Three Cases (2019)
Buried bumper syndrome (BBS) was described as a complication of percutaneous endoscopic gastrostomy (PEG) that occurs when the internal stump of the probe migrates and is located between the gastric wall and the skin. The increase of compression between the internal stump and the external stump of the gastrostomy tube causes pain and the inability to feed. We present the cases of three patients with BBS managed by the metabolic and nutritional support department. These cases intend to illustrate one of the less frequent complications of PEG, clinical presentation, risk factors, diagnosis, and especially clinical management. Although there are no defined gold standards for its management, the most important points in the management of this condition are early recognition, recommendations to avoid ischemic process at the moment of the insertion of the tube, specific care of the gastrostomy tube, and a periodic nutrition evaluation to avoid overweight, which causes traction and excessive pressure in the gastric wall. It is important for physicians to be aware of the recommendations to prevent BBS and its complications, especially in patients in whom communication can be difficult secondary to their pathologies and comorbidities.